Desarrollo de un dispositivo electromecánico para identificar según la tonalidad de la epidermis los frutos del cafeto cosechados. - Pupiales Ordóñez, Cristian Fernando (2023)
As an alternative to the conventional manual selection method currently used in the environment, this study illustrates the design of an electromechanical device that identifies harvested coffee berries by their epidermis color. The project started by identifying the components for the operation of the device, by means of a bibliographic search on the physical characteristics of the product to be classified and the evaluation of industrial machines that carry out the classification by color, obtaining the general proposal for the design of an automatic system for the recognition of fruits by color, based on a chain conveyor. By defining the requirements, the control circuit and mechanical components of the device were developed, followed by the selection of elements, and concluded with the design of the components, namely the container, the rails, the identification booth, the ejectors, the roller chain conveyor, and the Raspberry Pi control board. As a result of the implementation of the identification device in a prototype, the confusion matrix metrics were used to validate the results, resulting in 49.32% accuracy, 44.45% accuracy, 46.76 % overall performance, classified into five categories, with a speed of 23.07 g/min. Even though the device had low performance, it stood out for its ability to classify in the most categories, compared to previous works. Keywords: coffee, color sorting, sorter prototype, roller conveyor.